The dynamic relationship among technological innovation, international trade, and energy production - Zhang, Min; Jain, Vipin; Qian, Xinze; Ramos-Meza, Carlos Samuel; Ali, Syed Ahtsham; Sharma, Paritosh; Ahmed Mohamed, Mady Ahmed; Haddad, Akram M.; Shabbir, Malik Shahzad (Frontiers in Environmental Science, 2023)
The primary objective of this study is to analyze the dynamic association among the green energy production (GEP), green technological innovation (GTI), and green international trade (GIT). This study uses fully modified least square (FMOLS) and dynamic least square (DOLS) for data analysis. This study uses the panel data set starts from 2000 to 2020 for eight south Asian countries. This study find a negative relationship between GEP and EFP. However, green technological innovation and green international trade have positive significant association. This study recommends several policy implications regarding the economies of south Asia (SA) based on empirical findings: to subsidize the industries for the installation of renewable projects for the production of renewable energies.